Penerapan Pembelajaran Blended Learning Dengan Model Pembelajaran Berbasis Masalah Untuk Meningkatkan Kemandirian Belajar Akuntansi Siswa Kelas X Akuntansi SMK Batik 2 Surakarta Tahun Ajaran 2016/2017 - Purwantini, Septiana Susi; , Agus Susilo, S.Pd., M.Pd (2017)
Septiana Susi Purwantini/ A210130033. THE IMPLEMENTATION OF BLENDED LEARNING WITH PROBLEM-BASED LEARNING MODEL TO IMPROVE THE INDEPENDENCE OF ACCOUNTING LEARNING STUDENTS CLASS X ACCOUNTING SMK BATIK 2 SURAKARTA IN THE ACADEMIC YEAR 2016/2017. Essay. Teacher Training and Education Faculty, Muhammadiyah University of Surakarta. May, 2017. The purpose of this study is to improve the independence of accounting learning through blended learning with problem-based learning model. The type of this research is Classroom Action Research (PTK) done in 2 cycles. The subjects of this study are teachers and students of class X Accounting 1 SMK Batik 2 Surakarta, consist of 39 students. Data collection methods are documentation, interview, observation and questionnaire. The data analysis techniques use methods that include data reduction, data presentation and conclusions or verification. The results showed an increase in the independence of accounting learning. It can be seen through the following indicators. 1) confident in learning before action 41,03% and after action become 82,05%; 2) active in learning before action 46,15% and after action become 89,74%; 3) discipline in learning before action 51, 28% and after action became 97,44%, 4) responsibility in learning before action 43,59% and after action became 87,18%, and 5) motivation in learning before action 30,77% and after action became 76,92 %. The conclusion of this research is blended learning with problem-based learning model can improve student accountancy independence class X Accounting 1 SMK Batik 2 Surakarta Academic Year 2016/2017.